A Property Rights View: Commentary on “Property and Speech” by Robert A. Sedler - Shelley Ross Saxer (Washington University Journal of Law & Policy, 2006)
I begin by exploring whether the First Amendment, as a sword, obscures the difference between state and private action by constitutionally preventing private property owners from interfering with an individual’s free expression rights. Thus, private property owners, who are not otherwise held to constitutional standards, cannot block activities of others that invade their property interests because these activities are protected by the First Amendment. This Commentary will address an additional category, not mentioned by Professor Sedler in his Essay—the government’s use of eminent domain, which can be used as a “sword” against land uses protected by the First Amendment.
Keywords: First Amendment protections (United States Constitution); Eminent domain (Law); Freedom of speech; Property rights; United States Constitution; United States